1985
DOI: 10.1002/1097-0142(19850315)55:6<1190::aid-cncr2820550609>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid dysfunction and neoplasia in children receiving neck irradiation for cancer

Abstract: The reported relationship of radiation exposure and thyroid carcinoma stimulated this retrospective study of 298 patients treated at St. Jude Children's Hospital with radiation therapy to the neck for childhood cancer to identify patients who developed subsequent thyroid abnormalities. This series includes 153 patients with Hodgkin's disease, 95 with acute lymphocytic leukemia, 28 with lymphoepi‐thelioma, and 22 with miscellaneous tumors. Inclusion in the study required 5 years of disease‐free survival followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(23 citation statements)
references
References 24 publications
(1 reference statement)
0
23
0
Order By: Relevance
“…This is in agreement with the findings of Fleming et al (1985). However, some studies have shown an increase in thyroid dysfunction associated with lymphangiography (Kaplan et al, 1983), whereas others have shown a protective effect (Green et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with the findings of Fleming et al (1985). However, some studies have shown an increase in thyroid dysfunction associated with lymphangiography (Kaplan et al, 1983), whereas others have shown a protective effect (Green et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Irradiation of the thyroid gland has been associated with development of compensated hypothyroidism, overt hypothyroidism, thyroiditis and thyroid neoplasms. 1 After irradiation the onset of thyroid dysfunction often begins as compensated hypothyroidism with elevated thyroid-stimulating hormone (TSH) and normal thyroid hormone production, but then may progress to overt hypothyroidism over the next several decades. Hypothyroidism contributes to decreased height growth in children.…”
Section: Thyroid Functionmentioning
confidence: 99%
“…Studies on patients receiving irradiation treatment for various cancers have reported a high frequency of benign and malignant thyroid nodules. The reported relative risks for thyroid nodules among the survivors of pediatric cancers who have undergone radiation therapy vary greatly, with an incidence of malignancy of 10-40% (6,7,8,9,10,11,12,13). Analysis of studies evaluating thyroid carcinoma after exposure to external radiation during childhood showed that the dose-response relationship was linear, although the risk appeared to plateau at the highest dose, with risk appearing to slightly decrease at doses of even more than 2000 cGy (9,11,13,14,15,16).…”
Section: Introductionmentioning
confidence: 99%